Antibacterial and Antifungal Effect of Eupatorium adenophorum Spreng against Bacterial and Fungal Isolates - Bhattarai, Nabin; Shrestha, Geeta (Nepal Journal of Science and Technology, 2010)
A research work on antimicrobial effect of water solvent and organic solvent extracts of different concentration of Eupatorium adenophorum (Spreng) was conducted at Nepal Academy of Science and Technology (NAST) during August 2008. Fifteen strains of bacteria, six strains of fungi and two concentrations, 50% and 100% of plant extracts were taken for the study. Among the 15 strains of bacteria, most of them were inhibited with E. adenophorum extracts and only three species, Klebsiella oxytoca, K. pneumoniae and Shigella dysenteriae did not show antibacterial activity with the same extract. Extracts obtained from the organic solvent and water solvent showed different antimicrobial properties with the same bacterial strains. Those bacterial strains whose growth was inhibited by water solvent could not inhibited by organic solvent extracts. Organic solvent extract showed antibacterial effect towards Proteus spp., Salmonella spp., Staphylococcus spp., Bacillus subtilis, B. thurengiensis, B. cereus, Enterobacter aerogenes, Salmonella paratyphi, Staplococcus aureus, Proteus mirabilis and water solvent extract showed antibacterial effect towards Peudomonas aeruginosa, E. coli, Staphylococcus aureus, Staphylococcus spp., Citrobacter frundii, Proteus spp., B. subtilis, B. thurengiensis, Enterobacter aerogenes, Salmonella spp. and S. paratyphi. Altogether 12 species out of 15 were inhibited by E. adenophorum extracts. Both solvent extracts showed high antibacterial effect towards Proteus spp., Staphylococcus spp., Staphylococcus aureus and Pseudomonas aeruginosa. Among the six species of the fungi, Fusarium spp. were inhibited by plant extract while the Aspergillus spp. and Stenophylum botryosum did not show any effect of the extracts. The plant extracts showed selective effect with different strains of bacteria and fungi, which indicated that they were confined to cure the same bacterial diseases and fungal diseases. Key words: Plant extract; Bacteria; Fungi; Antibacterial; Antifungal; Eupatorium adenophorum DOI: 10.3126/njst.v10i0.2834 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 91-95